Sustainable economic development: a criminal justice challenge for the 21st century - Hoffman, Joan (Crime, law and social change, 2000)
The environmental challenges of the 21st century require co-operation between criminal justice experts and economists. Three different economics perspectives are relevant for the discipline of criminal justice in general and for adressing environmental problems in particular: neo-classical econoics, political economics and the economics of sustainable development. Criminal justice pays a role in the effort to attain sustainable development because the limitations of market based decision making necessitate a role for law and regulation in addressing environmental degradation. Sustainable development itself is relevant to the general discussion of crime. Issues of sustainable development are already discussed in criminal justice literature. While criminal law has limitations as a tool against environmental crime, it will necessarily suplement the tools of the market and civil regulation in coping with environmental problems. The inherently multidisciplinary undertaking of sustainable development will be most effectively met if experts in both economics and criminal justice understand more of one another's fields. Suggestions for including the three perspectives of economics in the criminal justice curriculum are provided.